2008
DOI: 10.1021/bi8000566
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Enzyme Regulation by Multiple Allosteric Effectors: Nucleotide Regulation of Aspartate Transcarbamoylase

Abstract: The enzyme aspartate transcarbamoylase (ATCase, EC 2.1.3.2 of Escherichia coli), which catalyzes the committed step of pyrimidine biosynthesis, is allosterically regulated by all four ribonucleoside triphosphates (NTPs) in a nonlinear manner. Here, we dissect this regulation using the recently developed approach of random sampling-high-dimensional model representation (RS-HDMR). ATCase activity was measured in vitro at 300 random NTP concentration combinations, each involving (consistent with in vivo condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Crystallography studies have shown that the ribose triphosphate portions of ATP and CTP bind in essentially the same part of the nucleotide-binding site. Therefore one might expect to also observe an interaction of the enzyme with other nucleotides such as UTP and GTP, although it has been reported that these nucleotides do not alter the activity of the enzyme alone or in nucleotide combinations (19). Nevertheless, UTP or GTP alone was able to drastically alter the fluorescence intensity of the HCE-Gly52 R ATCase (Figure 3, panel b ; Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Crystallography studies have shown that the ribose triphosphate portions of ATP and CTP bind in essentially the same part of the nucleotide-binding site. Therefore one might expect to also observe an interaction of the enzyme with other nucleotides such as UTP and GTP, although it has been reported that these nucleotides do not alter the activity of the enzyme alone or in nucleotide combinations (19). Nevertheless, UTP or GTP alone was able to drastically alter the fluorescence intensity of the HCE-Gly52 R ATCase (Figure 3, panel b ; Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…ATCase, the primary regulatory enzyme of de novo pyrimidine biosynthesis, is allosterically regulated by ATP availability thereby functioning as a cellular energy sensor input to this pathway. In addition to its enzymatic activity being positively regulated by a purine (ATP), ATCase is negatively regulated by a pyrimidine (CTP), enabling its critical function of maintaining nucleotide pool balance between purines and pyrimidines 19,20 . Nucleotide pool balance is a key determinant of DNA replication fidelity.…”
Section: Discussionmentioning
confidence: 99%
“…There were also responsive proteins in the decreased manner associated with biosynthesis and cellular processes (Fig. and Table ), which included l ‐aspartate oxidase (NadB), a ubiquitous enzyme for the de novo biosynthesis of NAD + as a signalling molecule in a variety of cellular processes; Aspartate carbamoyltransferase (PyrB), a key enzyme in the first committed step of de novo pyrimidine biosynthesis that plays a critical role in cellular metabolism serving as activated precursors of RNA and DNA, CDP‐diacylglycerol phosphoglyceride for the assembly of cell membranes and UDP‐sugars for protein glycosylation and glycogen synthesis; and acetylglutamate kinase (ArgB), a member of the amino acid kinase family, which catalyses the second and frequently controlling step of arginine synthesis . Furthermore, the proteomics data revealed that the abundances of key proteins associated with transcription and translation were reduced, such as RNA polymerase sigma factor (RpoD), ribosomal proteins (RpsA and RplJ) and phenylalanyl‐tRNA synthetase (PheS) (Fig.…”
Section: Discussionmentioning
confidence: 99%